THE IMPLEMENTATION OF JIGSAW TECHNIQUE TO IMPROVE STUDENTS’ PARTICIPATION IN LEARNING ENGLISH SPEAKING - Rika, Prisilla; Regina, Regina; Husin, Syarif (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of this research is to improve the students’ participation in learning English speaking through the use of Jigsaw technique. The method used is Classroom Action Research which consisted of 2 cycles. To collect the data, the writer used observation checklist, field notes and the table of participation grade to reflect the students’ improvement in participation of each cycle. The subject of this research was the tenth grade students of SMAN 5 Pontianak. The writer provided the students’ mean score from the table of participation grade and the result of observation checklist, and field notes at the end of lesson. From the result of the observation checklist and field notes, it was found that in the first cycle most of students showed less participation, on the other hand in the second cycle most of students showed a good participation in learning English speaking through the use of Jigsaw technique. It can also be concluded from the result of the table of participation grade, it was found that in the first cycle, the mean score was 53 points which was classified into poor to average. And in the second cycle, the mean score was 74 which was classified into average to good. In conclusion, the students’ participation of the tenth grade students of SMAN 5 Pontianak has improved through the use of Jigsaw technique. Key words: Jigsaw, Speaking, Participation